Comin' down to storytime - Reid, Rob.; Westcott, Nadine Bernard (Janesville, WI : Upstart Books, 2009)
"Storytime! That's all the little barnyard animals need to hear to send them flocking to their librarian, who has some rip-roaring, song-singing, nursery-rhyming, snack- timing fun in store for them! You've never seen a storytime quite like this...and reading has never been such fun!. Set to the tune of 'She'll be comin' round the mountain when she comes.'"--Jacket.
Includes pbk.: Library lessons with activity program ideas and bibliographical references.
Keywords: Domestic animals -- Songs and music -- Juvenile literature; Librarians -- Songs and music -- Juvenile literature; Storytelling -- Songs and music -- Juvenile literature; Domestic animals -- Songs and music; Librarians -- Songs and music; Storytelling -- Songs and music